2020
DOI: 10.1007/s00103-020-03213-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatische Erkrankungen Wohnungsloser in Deutschland. Ein narratives Literaturreview der Jahre 2009–2019

Abstract: Zusammenfassung Hintergrund In Deutschland leben Schätzungen zufolge zwischen 337.000 und 650.000 wohnungslose Menschen in gesundheitlich zumeist prekärer Lage. Studien zu ihrer Gesundheit sind selten und methodisch heterogen. Bisherige Übersichtsarbeiten fokussierten auf psychische Erkrankungen. Fragestellung Ziel der Arbeit ist es, einen Überblick über die aktuelle Forschung zu somatischen Erkrankungen von Wohnungslosen in Deutschland zu geben. Methoden Auf Grundlage einer systematischen Literaturrecher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
5
1
6
Order By: Relevance
“…Existing studies show stark health discrepancies of PEH when compared to people in secure living situations. For instance, a systematic review from 2020 reveals a higher prevalence of cardiovascular, musculoskeletal, and respiratory diseases among PEH compared to the population in secure housing in Germany (4). A meta-analysis from 2017 draws a similar picture: mental health problems among PEH are considerably higher as compared to people in secure housing.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies show stark health discrepancies of PEH when compared to people in secure living situations. For instance, a systematic review from 2020 reveals a higher prevalence of cardiovascular, musculoskeletal, and respiratory diseases among PEH compared to the population in secure housing in Germany (4). A meta-analysis from 2017 draws a similar picture: mental health problems among PEH are considerably higher as compared to people in secure housing.…”
Section: Introductionmentioning
confidence: 99%
“…Another strength includes the study design, as longitudinal data is available for a long period of time (14 years) and for a large, representative population (about 3 000 medical records). As no inclusion criteria are applied, a broad range of social and health situations will be analysed, including marginalised groups in research such as women and young patients (48). Further, a big strength of the present study is the consideration of the course of time for both cross sectional analysis (analysis of trends) and longitudinal analysis (inter and intra individually) of data.…”
Section: Discussionmentioning
confidence: 99%
“…Further, homeless people are di cult to sample which limits most research and results in small and highly selected samples. A recent review found that previous research is highly selective were participants are often older, male and from a subgroup setting as for example from supervised drug consumption facilities (48). Thus, there is a clear lack of investigation among women and younger individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Obdachlose Menschen weisen bspw. erhöhte Prävalenzraten in den Bereichen der psychischen Störungen 3 4 , Infektionskrankheiten 5 und anderen somatischen Erkrankungen 6 7 auf. Auch ist Drogenmissbrauch recht häufig 8 .…”
Section: Introductionunclassified